Avaliação dos impactos ambientais da fabricação de um módulo fotovoltaico de silício policristalino - Bastos, Rodrigo (2020)
Investment in renewable sources of electrical energy has been growing exponentially in the world, mainly with the aim of reducing the environmental impact caused by non-renewable and highly polluting sources, such as oil and coal. Among the sources renewable sources, photovoltaic solar energy has stood out as an excellent alternative to meet energy needs. This research sought to evaluate and analyze the impacts environmental issues related to the manufacturing of the polycrystalline silicon photovoltaic module. The panel manufacturing was analyzed from obtaining the production raw material, through silicon extraction, proceeding to the stages of obtaining metallurgical grade silicon, purification of solar grade silicon, manufacturing of ingots and wafers, manufacturing of the cell photovoltaic and panel, featuring a cradle-to-gate approach. Added to this process, the characterization of impacts for the transport stage to the installation destination of the panel. To achieve this objective, Life Cycle Assessment (LCA) was used by using SimaPro software to analyze the impacts generated throughout the production chain of panel and its transportation. To implement the LCA, 3 scenarios were modeled. In scenario 1 it was considered the total manufacture of the photovoltaic panel in China with its transportation to the Brazil. Scenario 2 was evaluated considering wafer manufacturing in China and transportation sent to Brazil for subsequent manufacturing of the cell and panel. In scenario 3, the idea was to complete manufacturing of the panel in Brazil. The impacts generated through the Impact 2002+ assessment methodology that characterized the impacts on 14 indicators of midpoint and 4 end point indicators. The evaluation metrics of Accumulated Energy Demand, Energy Payback Time and Emission of Gases Greenhouse Effect. The evaluation of all indicators in the 3 scenarios showed that the production of photovoltaic panel in Brazil (scenario 3) is the one with the lowest value in terms of impacts evaluated.